Model Usahatani Integrasi Tanaman Sereh Wangi Menjadi Minyak Atsiri dan Ternak Sapi di Kabupaten Ogan Ilir - Henny Malini; Eka Mulyana; Friska Syaiful (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2022)
This study aims to identify the farming model and calculate the Financial Feasibility of the integration of Citronella and cattle in the Ogan Ilir Regency. The location determination was carried out purposively because in this district there is a community business of Citronella Oil Refining combined with cattle business (plant - livestock integration) in Indralaya District, Ogan Ilir Regency. The research method is a case study, the first objective is identified and then described in a diagram and descriptive manner. the second objective is analyzed mathematically by calculating the BC/RC Ratio, Payback Period, NPV, and IRR. The Integration Model of Citronella Plants and cattle is an integrated farming model, a business model that is interrelated with each other, where the waste from the Citronella plant can be utilized, as well as cow dung. Based on the financial feasibility analysis, the Gross B/C value produced is 2.07 and the Net B/C is also 2.30. The resulting Payback Period value is 4 years, BEP (kilogram) is 503.69 kg and BEP (Rupiah) is Rp. 125,923,822, while based on the feasibility analysis of cattle business in Ogan Ilir Regency, the Gross B/C value obtained is 1, 44, and Net B/C of 1.44. The resulting Payback Period value is 2.2 years, BEP (unit) is 33 heads and BEP (Rupiah) is 294,160,182, - So it can be concluded that fragrant lemongrass farming and cattle farming are financially feasible.Keywords: Feasibility, Financial, Integration, Lemongrass, Model.